Leakage Detection in Pipeline Using Synchrosqueeze Wavelet Transform - Makeen, Mohd Amin; Abdul, Hadi; M. F., Ghazali (Elsevier, 2013)

(untitled)
The detection of water leakages in water distribution system has always been a challenge in the water industry as most water pipelines are laid foot underground which are normally unseen to human naked eyes until water starts to flow out from roads and creates puddles. The age in pipelines network is a major problem and the reduction of these has become a major priority for pipeline authorities around the world. This project method are developed based on pressure transient by using single pressure transducer and analyses on newly method of analyzing called synchrosqueeze wavelet transform (SWT) which is viable approach to detect and locate the leak in pipeline system. Transient analyses offer a plausible route towards leak detection due to their robustness and simplicity. The result show that newly developed techniques, SWT appears to improve the ability of the method to identify features in the signal. © (2014) Trans Tech Publications, Switzerland.